Las Criptomonedas En Colombia Y Su Marco Contable Según Las Normas Internacionales De Información Financiera (Niif) (2024)
This project developed topics that concern the new technological advances that the world has had to this day, one of these advances is the creation of cryptocurrencies that have been generating great development and acceptance in the financial market in order to reduce costs, shortening distances, among other advantages; But at the same time, the creation of this type of currency has brought with it controversy because it does not have current regulations in the world, especially in Colombia. Apart from that, its accounting framework has had flaws and/or difficulties since due to the characteristics of Cryptocurrencies do not have a classification within the International Financial Reporting Standards, which affects their management, adding that because they are a type of decentralized currency and they do not have surveillance by any entity, illicit activities such as scams have been carried out in which The users who invest in these are affected; additionally, during the development of this work, concepts issued by Colombian entities such as La DIAN, the CTCP, the Financial Superintendence, among others, have been taken into account. The main objective of this study was to understand the functioning of cryptocurrencies in Colombia and their accounting framework according to the International Financial Reporting Standards - IFRS. The approach used in this work corresponds to qualitative research covering the documentary research method since the collection of information for this was carried out by obtaining theoretical supports from other theses on the topic of cryptocurrencies. Finally, this study informs Colombians about how to establish an accounting framework according to the economic activity carried out with this digital currency and based on the International Financial Reporting Standards (IFRS).